Antimicrobial susceptibilities of Lactococcus lactis and Lactococcus garvieae and a proposed method to discriminate between them. - Elliott, J A (1996)
The MICs of antimicrobial agents contained in the SCEPTOR Streptococcus MIC panels (Becton Dickinson Microbiology Systems) were determined for Lactococcus lactis, L. garvieae, and unknown Lactococcus species. Several isolates had reduced susceptibilities to many of the antimicrobial agents contained in the panel. For L. garvieae, the MICs of penicillin and, possibly, cephalothin were higher than for L. lactis, and unlike L. lactis, L. garvieae was resistant to clindamycin, indicating that knowledge of the Lactococcus species causing an infection might influence the choice of antimicrobial therapy. Susceptibility to clindamycin can also be used to differentiate between L. lactis and L. garvieae.